What is functional mobility applied to Parkinson’s disease? - Bouça-Machado, Raquel (2018)
© 2018 – IOS Press and the authors. All rights reserved. This article is published online with Open Access and distributed under the terms of the Creative Commons Attribution Non-Commercial License (CC BY-NC 4.0).